The role of KCC2 and NKCC1 in spinal cord injury: From physiology to pathology - Talifu, Zuliyaer; Pan, Yunzhu; Gong, Han; Xu, Xin; Zhang, Chunjia; Yang, Degang; Gao, Feng; Yu, Yan; Du, Liangjie; Li, Jianjun (Frontiers in Physiology, 2022)
The balance of ion concentrations inside and outside the cell is an essential homeostatic mechanism in neurons and serves as the basis for a variety of physiological activities. In the central nervous system, NKCC1 and KCC2, members of the SLC12 cation-chloride co-transporter (CCC) family, participate in physiological and pathophysiological processes by regulating intracellular and extracellular chloride ion concentrations, which can further regulate the GABAergic system. Over recent years, studies have shown that NKCC1 and KCC2 are essential for the maintenance of Cl− homeostasis in neural cells. NKCC1 transports Cl− into cells while KCC2 transports Cl− out of cells, thereby regulating chloride balance and neuronal excitability. An imbalance of NKCC1 and KCC2 after spinal cord injury will disrupt CI− homeostasis, resulting in the transformation of GABA neurons from an inhibitory state into an excitatory state, which subsequently alters the spinal cord neural network and leads to conditions such as spasticity and neuropathic pain, among others. Meanwhile, studies have shown that KCC2 is also an essential target for motor function reconstruction after spinal cord injury. This review mainly introduces the physiological structure and function of NKCC1 and KCC2 and discusses their pathophysiological roles after spinal cord injury.